Identifying the Characteristics of Geriatric Patients who Referred to Outpatient Clinics of Physical Medicine and Rehabilitation: A Multicenter Descriptive Study - YAĞCI, İLKER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2011)
Aim: The aim of this study was to define the demographic and clinical characteristics of geriatric patients who referred to physical medicine and rehabilitation (PMR) outpatient clinics and to detect the differences between these characteristics in regard to age, sex and education level. Materials and Methods: 820 patients over 65 years old who attended 20 outpatient clinics were included in the study. In addition to demographic data, the complaints, comorbid diseases, pain levels, drugs being used, exercise and medical status of the patients were recorded. The effects of age, sex and education level on complaints, comorbid diseases and exercise habits were investigated. Results: The mean age of the patients was 71.7 +/- 5.5 years. 16.7% were living alone, 61.7% were housewives. 86% of the patients had one or more comorbid diseases - hypertension, gastric problems and heart disease were mostly encountered. The most common complaints were joint pain, fatigue and widespread body pain. The average number of pills taken per day was 4.02 +/- 0.9 (median 4), and the VAS pain score was 5.1 +/- 1.3 (median 5.0). History of falling was present in 16.5% of patients. 30.1% were routinely walking and 15.4% were performing exercise at home. In patients over 75 years, vertebral pain and deformity, urinary incontinence, eye problem, difficulty in swallowing, decrease in hearing, as well as balance and teeth problems were significantly more frequent than in younger subjects. Conclusion: Aged population constitutes most of the PMR outpatient clinic patients. Considering comorbid diseases, high number of daily taken drugs and falls, PMR specialist should be cautious in prescribing drugs and planning rehabilitation programme. For independence in activities of daily living in this age group, besides the musculoskeletal system, all other systems should be evaluated and a comprehensive geriatric rehabilitation programme should be constructed. Turk J Phys Med Rehab 2011;57:143-9.
Keywords: Elderly; sex; comorbid diseases; polypharmacy; BONE LOSS; WOMEN; MEN; DISEASES